A review of failure modes of nuclear fuel cladding - Khattak M.A.; Omran A.A.B.; Kazi S.; Khan M.S.; Ali H.M.; Tariq S.L.; Akram M.A. (Taylor's University, 2023)
In this research, an effort has been made to systematically establish the research studies managed on an assortment of nuclear fuel cladding materials since the initial reactors, revealing some of the main failure modes and briefly reflecting the challenges facing the progress of fuel cladding materials and clad tube failure for the future generation of reactors. An introduction to various clad materials has been added, in which, the result of alloying elements on the material properties have been presented. Each subsection of the review has been provided with some tables and figures. The small part on determining a good fuel clad has also been encompassed. The last section of the review has been devoted to accidents occur related to fuel clad. About 101 published studies (1965-2017) are examined in this review. It is noticeable from the review of articles that increase in corrosion and creep rate during Loss of Coolant Accident (LOCA) are significant. During corrosion, oxide layers formed on the clad surface are brittle, which would endanger the structural integrity. Creep deformation cause cladding tube ballooning. School of Engineering, Taylors University.